Pantograph/experiments/dsp/debug/toy_example1_dsp/dsp_debug4_sf.json

368 lines
20 KiB
JSON
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

[
{
"nl_problem": "For any natural number n, n + 0 = n.",
"nl_solution": [
"Consider some natural number n. We want to show n + 0 = n. ",
"By using fats of addition on both sides, LHS and RHS are now equal, done."
],
"fl_problem": "theorem n_plus_zero : ∀ n : , n + 0 = n := by",
"fl_solution": [
"-- Prove that n + 0 = n.\n",
"theorem n_plus_zero : ∀ n : , n + 0 = n := by\n",
" -- Consider some n in Nats.\n",
" intro n",
"-- Using facts of addition simplify n + 0 to n.\n",
" rw [Nat.add_zero]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic"
],
"nl_problem_proved_sketch": "For any natural number n, n + 0 = n.",
"nl_solution_proved_sketch": [
"We want to show n + 0 = n. ",
"We have the fact of addition that, n + 0 = n. ",
"Thus, the left-hand side and right-hand side are equal, which completes the proof."
],
"fl_problem_proved_sketch": "theorem n_plus_zero_proved_formal_sketch : ∀ n : , n + 0 = n := by",
"fl_solution_proved_sketch": [
"-- Prove that n + 0 = n via a formal proof sketch",
"theorem n_plus_zero_proved_formal_sketch : ∀ n : , n + 0 = n := by",
" -- We have the fact of addition n + 0 = n, use it to show left and right are equal.",
" have h_nat_add_zero: ∀ n : , n + 0 = n := Nat.add_zero",
" exact h_nat_add_zero"
],
"src_header_fl_solution_proved_sketch": ["import Mathlib.Data.Nat.Basic"],
"nl_problem_proved_sketch_aesop": "For any natural number n, n + 0 = n.",
"nl_solution_proved_sketch_aesop": [
"We want to show n + 0 = n. ",
"We have the fact of addition that, n + 0 = n. ",
"Thus, the left-hand side and right-hand side are equal, which completes the proof."
],
"fl_problem_proved_sketch_aesop": "theorem n_plus_zero_proved_formal_sketch' : ∀ n : , n + 0 = n := by",
"fl_solution_proved_sketch_aesop": [
"-- Prove that n + 0 = n via a formal proof sketch with aesop. ",
"theorem n_plus_zero_proved_formal_sketch' : ∀ n : , n + 0 = n := by",
" -- We have the fact of addition n + 0 = n, use it to show left and right are equal. ",
" have h_nat_add_zero: ∀ n : , n + 0 = n := by aesop",
" exact h_nat_add_zero"
],
"src_header_fl_solution_proved_sketch_aesop": [
"import Mathlib.Data.Nat.Basic",
"import Aesop"
]
},
{
"nl_problem": "For any natural number n, 0 + n = n.",
"nl_solution": [
"Consider some natural number n. We want to show 0 + n = n.",
"By using facts of addition and induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem zero_plus_n : ∀ n : , 0 + n = n := by",
"fl_solution": [
"-- Prove that 0 + n = n by induction",
"theorem zero_plus_n : ∀ n : , 0 + n = n := by",
"-- Consider some n in Nats.",
"intro n",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: 0 + 0 = 0",
"rw [Nat.add_zero]",
"| succ n ih =>",
"-- Inductive step: assume 0 + n = n, prove 0 + succ n = succ n",
"rw [Nat.add_succ]",
"rw [ih]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic"
],
"nl_problem_proved_sketch": "For any natural number n, 0 + n = n.",
"nl_solution_proved_sketch": [
"We want to show 0 + n = n.",
"By using the fact of addition and performing induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem_proved_sketch": "theorem zero_plus_n_proved_formal_sketch : ∀ n : , 0 + n = n := by",
"fl_solution_proved_sketch": [
"-- Prove that 0 + n = n by induction via a formal proof sketch",
"theorem zero_plus_n_proved_formal_sketch : ∀ n : , 0 + n = n := by",
"-- Consider some n in Nats.",
"intro n",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: 0 + 0 = 0",
"have h_base: 0 + 0 = 0 := by rw [Nat.add_zero]",
"exact h_base",
"| succ n ih =>",
"-- Inductive step: assume 0 + n = n, prove 0 + succ n = succ n",
"have h_inductive: 0 + Nat.succ n = Nat.succ n := by",
"rw [Nat.add_succ]",
"rw [ih]",
"exact h_inductive"
],
"src_header_fl_solution_proved_sketch": [
"import Mathlib.Data.Nat.Basic"
],
"nl_problem_proved_sketch_aesop": "For any natural number n, 0 + n = n.",
"nl_solution_proved_sketch_aesop": [
"We want to show 0 + n = n.",
"By using the fact of addition and performing induction on n, we can prove the statement for both the base case and the inductive step using aesop."
],
"fl_problem_proved_sketch_aesop": "theorem zero_plus_n_proved_formal_sketch' : ∀ n : , 0 + n = n := by",
"fl_solution_proved_sketch_aesop": [
"-- Prove that 0 + n = n by induction via a formal proof sketch with aesop.",
"theorem zero_plus_n_proved_formal_sketch' : ∀ n : , 0 + n = n := by",
"-- Consider some n in Nats.",
"intro n",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: 0 + 0 = 0",
"have h_base: 0 + 0 = 0 := by aesop",
"exact h_base",
"| succ n ih =>",
"-- Inductive step: assume 0 + n = n, prove 0 + succ n = succ n",
"have h_inductive: 0 + Nat.succ n = Nat.succ n := by aesop",
"exact h_inductive"
],
"src_header_fl_solution_proved_sketch_aesop": [
"import Mathlib.Data.Nat.Basic",
"import Aesop"
]
},
{
"nl_problem": "For any natural numbers n and m we have commutativity, n + m = m + n.",
"nl_solution": [
"Consider some natural numbers n and m. We want to show n + m = m + n.",
"By using facts of addition and induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem add_comm_normal : ∀ n m : , n + m = m + n := by",
"fl_solution": [
"-- Prove that n + m = m + n",
"theorem add_comm_normal : ∀ n m : , n + m = m + n := by",
"-- Consider some n and m in Nats.",
"intros n m",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: When n = 0, we need to show 0 + m = m + 0.",
"-- Using the definition of addition, 0 + m = m and m + 0 = m.",
"rw [Nat.zero_add, Nat.add_zero]",
"| succ n ih =>",
"-- Inductive step: Assume n + m = m + n, we need to show succ n + m = m + succ n.",
"-- We use the fact n + (m + 1) = (n + m) + 1.",
"have plus_n_Sm_normal: ∀ n m : , n + (m + 1) = (n + m) + 1 := by",
" intros n m",
" rw [Nat.add_succ]",
"-- Apply the fact to rewrite succ n + m = (n + m) + 1.",
"rw [Nat.add_succ, Nat.add_zero]",
"rw [← ih]",
"rw [Nat.succ_add]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic"
]
},
{
"nl_problem": "For any natural numbers n and m, n + m = m + n.",
"nl_solution": [
"Consider some natural numbers n and m. We want to show n + m = m + n.",
"By using the fact of addition and performing induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem add_comm_proved_formal_sketch : ∀ n m : , n + m = m + n := by",
"fl_solution": [
"-- Prove that n + m = m + n via a formal proof sketch",
"theorem add_comm_proved_formal_sketch : ∀ n m : , n + m = m + n := by",
"-- Consider some n and m in Nats.",
"intros n m",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: When n = 0, we need to show 0 + m = m + 0.",
"-- We have the fact 0 + m = m by the definition of addition.",
"have h_base: 0 + m = m := Nat.zero_add m",
"-- We also have the fact m + 0 = m by the definition of addition.",
"have h_symm: m + 0 = m := Nat.add_zero m",
"-- Combining these, we get 0 + m = m + 0.",
"rw [h_base, h_symm]",
"| succ n ih =>",
"-- Inductive step: Assume n + m = m + n, we need to show succ n + m = m + succ n.",
"-- By the inductive hypothesis, we have n + m = m + n.",
"have h_inductive: n + m = m + n := ih",
"-- proof is:",
"-- We eventually want to flip n + m and simplify to make both sides the same. Thus,",
"-- 1. Note we start with: Nat.succ n + m = m + Nat.succ n, so, pull the succ out from m + Nat.succ n on the right side from the addition using addition facts Nat.add_succ.",
"have h_pull_succ_out_from_right: m + Nat.succ n = Nat.succ (m + n) := by rw [Nat.add_succ]",
"-- 2. then to flip m + S n to something like S (n + m) we need to use the IH.",
"have h_flip_n_plus_m: Nat.succ (n + m) = Nat.succ (m + n) := by rw [h_inductive]",
"-- 3. Now the n & m are on the correct sides Nat.succ n + m = Nat.succ (n + m), so let's use the def of addition to pull out the succ from the addition on the left using Nat.succ_add.",
"have h_pull_succ_out_from_left: Nat.succ n + m = Nat.succ (n + m) := by rw [Nat.succ_add]",
"-- Combining these, we get succ n + m = m + succ n.",
"rw [h_pull_succ_out_from_right, ←h_flip_n_plus_m, h_pull_succ_out_from_left]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic"
]
},
{
"nl_problem": "For any natural numbers n and m, n + m = m + n.",
"nl_solution": [
"Consider some natural numbers n and m. We want to show n + m = m + n.",
"By using the fact of addition and performing induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem add_comm_proved_formal_sketch_aesop : ∀ n m : , n + m = m + n := by",
"fl_solution": [
"-- Prove that n + m = m + n via a formal proof sketch with aesop.",
"theorem add_comm_proved_formal_sketch_aesop : ∀ n m : , n + m = m + n := by",
"-- Consider some n and m in Nats.",
"intros n m",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: When n = 0, we need to show 0 + m = m + 0.",
"-- We have the fact 0 + m = m by the definition of addition.",
"have h_base: 0 + m = m := by aesop",
"-- We also have the fact m + 0 = m by the definition of addition.",
"have h_symm: m + 0 = m := by aesop",
"-- Combining these, we get 0 + m = m + 0.",
"rw [h_base, h_symm]",
"| succ n ih =>",
"-- Inductive step: Assume n + m = m + n, we need to show succ n + m = m + succ n.",
"-- By the inductive hypothesis, we have n + m = m + n.",
"have h_inductive: n + m = m + n := by aesop",
"-- proof is:",
"-- We eventually want to flip n + m and simplify to make both sides the same. Thus,",
"-- 1. Note we start with: Nat.succ n + m = m + Nat.succ n, so, pull the succ out from m + Nat.succ n on the right side from the addition using addition facts Nat.add_succ.",
"have h_pull_succ_out_from_right: m + Nat.succ n = Nat.succ (m + n) := by aesop",
"-- 2. then to flip m + S n to something like S (n + m) we need to use the IH.",
"have h_flip_n_plus_m: Nat.succ (n + m) = Nat.succ (m + n) := by aesop",
"-- 3. Now the n & m are on the correct sides Nat.succ n + m = Nat.succ (n + m), so let's use the def of addition to pull out the succ from the addition on the left using Nat.succ_add.",
"have h_pull_succ_out_from_left: Nat.succ n + m = Nat.succ (n + m) := by rw [Nat.succ_add]",
"-- Combining these, we get succ n + m = m + succ n.",
"rw [h_pull_succ_out_from_right, ←h_flip_n_plus_m, h_pull_succ_out_from_left]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic",
"import Aesop"
]
},
{
"nl_problem": "Prove that for any natural numbers n, m, and p, n + (m + p) = (n + m) + p.",
"nl_solution": [
"Consider some natural numbers n, m, and p. We want to show n + (m + p) = (n + m) + p.",
"By using facts of addition and induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem add_assoc_normal : ∀ n m p : , n + (m + p) = (n + m) + p := by",
"fl_solution": [
"-- Prove that n + (m + p) = (n + m) + p",
"theorem add_assoc_normal : ∀ n m p : , n + (m + p) = (n + m) + p := by",
"-- Consider some n, m, and p in Nats.",
"intros n m p",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: When n = 0, we need to show 0 + (m + p) = (0 + m) + p.",
"-- Using the definition of addition, 0 + (m + p) = m + p and (0 + m) + p = m + p.",
"rw [Nat.zero_add, Nat.zero_add]",
"| succ n ih =>",
"-- Inductive step: Assume n + (m + p) = (n + m) + p, we need to show succ n + (m + p) = (succ n + m) + p.",
"-- proof strategy is, we move succ n out (or in) enough times then use the IH until both sides are the same.",
"-- 1. let's start by pulling out the succ from the left side and have the entire addition inside the succ.",
"rw [Nat.succ_add]",
"-- 2. Now that we have the IH hypothesis appearing inside the left, let's apply it so we have n + (m + p) = (n + m) + p.",
"rw [ih]",
"-- 3. Now that the parentheses (apps of plus) are in the right place for both sides, push the succ on the left twice so both terms are the same.",
"rw [← Nat.succ_add, ← Nat.succ_add]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic"
]
},
{
"nl_problem": "Prove that for any natural numbers n, m, and p, n + (m + p) = (n + m) + p.",
"nl_solution": [
"Consider some natural numbers n, m, and p. We want to show n + (m + p) = (n + m) + p.",
"By using facts of addition and induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem add_assoc_proved_formal_sketch : ∀ n m p : , n + (m + p) = (n + m) + p := by",
"fl_solution": [
"-- Prove that n + (m + p) = (n + m) + p",
"theorem add_assoc_proved_formal_sketch : ∀ n m p : , n + (m + p) = (n + m) + p := by",
"-- Consider some n, m, and p in Nats.",
"intros n m p",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: When n = 0, we need to show 0 + (m + p) = (0 + m) + p.",
"-- Using the definition of addition, 0 + (m + p) = m + p and (0 + m) + p = m + p.",
"rw [Nat.zero_add, Nat.zero_add]",
"| succ n ih =>",
"-- Inductive step: Assume n + (m + p) = (n + m) + p, we need to show succ n + (m + p) = (succ n + m) + p.",
"-- proof strategy is, we move succ n out (or in) enough times then use the IH until both sides are the same.",
"-- 1. let's start by pulling out the succ from the left side and have the entire addition inside the succ.",
"have h_pull_add_succ_out_from_left: Nat.succ n + (m + p) = Nat.succ (n + (m + p)) := by rw [Nat.succ_add]",
"-- 2. Now that we have the IH hypothesis appearing inside the left, let's apply it so we have n + (m + p) = (n + m) + p.",
"have h_inside_left_associates: Nat.succ (n + (m + p)) = Nat.succ ((n + m) + p) := by rw [ih]",
"-- 3. Now that the parentheses (apps of plus) are in the right place for both sides, push the succ on the left twice so both terms are the same.",
"have h_push_succ_in_left_twice: Nat.succ ((n + m) + p) = ((Nat.succ n) + m) + p := by rw [← Nat.succ_add, ← Nat.succ_add]",
"-- Combining these, we get succ n + (m + p) = (succ n + m) + p.",
"rw [h_pull_add_succ_out_from_left, h_inside_left_associates, h_push_succ_in_left_twice]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic"
]
},
{
"nl_problem": "Prove that for any natural numbers n, m, and p, n + (m + p) = (n + m) + p.",
"nl_solution": [
"Consider some natural numbers n, m, and p. We want to show n + (m + p) = (n + m) + p.",
"By using facts of addition and induction on n, we can prove the statement for both the base case and the inductive step."
],
"fl_problem": "theorem add_assoc_proved_formal_sketch_aesop : ∀ n m p : , n + (m + p) = (n + m) + p := by",
"fl_solution": [
"-- Prove that n + (m + p) = (n + m) + p via a formal proof sketch with aesop",
"theorem add_assoc_proved_formal_sketch_aesop : ∀ n m p : , n + (m + p) = (n + m) + p := by",
"-- Consider some n, m, and p in Nats.",
"intros n m p",
"-- Perform induction on n.",
"induction n with",
"| zero =>",
"-- Base case: When n = 0, we need to show 0 + (m + p) = (0 + m) + p.",
"-- Using the definition of addition, 0 + (m + p) = m + p and (0 + m) + p = m + p.",
"rw [Nat.zero_add, Nat.zero_add]",
"| succ n ih =>",
"-- Inductive step: Assume n + (m + p) = (n + m) + p, we need to show succ n + (m + p) = (succ n + m) + p.",
"-- proof strategy is, we move succ n out (or in) enough times then use the IH until both sides are the same.",
"-- 1. let's start by pulling out the succ from the left side and have the entire addition inside the succ.",
"have h_pull_add_succ_out_from_left: Nat.succ n + (m + p) = Nat.succ (n + (m + p)) := by rw [Nat.succ_add]",
"-- 2. Now that we have the IH hypothesis appearing inside the left, let's apply it so we have n + (m + p) = (n + m) + p.",
"have h_inside_left_associates: Nat.succ (n + (m + p)) = Nat.succ ((n + m) + p) := by aesop",
"-- 3. Now that the parentheses (apps of plus) are in the right place for both sides, push the succ on the left twice so both terms are the same.",
"have h_push_succ_in_left_twice: Nat.succ ((n + m) + p) = ((Nat.succ n) + m) + p := by rw [← Nat.succ_add, ← Nat.succ_add]",
"-- Combining these, we get succ n + (m + p) = (succ n + m) + p.",
"rw [h_pull_add_succ_out_from_left, h_inside_left_associates, h_push_succ_in_left_twice]"
],
"src_header_fl_solution": [
"import Mathlib.Data.Nat.Basic",
"import Aesop"
]
}
]